The effects of experimental program on the explosive strength of lower limbs in male adolescents - Nikola Radulović; Mila V. Jurišić; Ratko Pavlović; Jelena Obradović; Ilona Mihajlović (IP Iermakov S.S., 2022)
Background and Study Aim. Various experimental programs for the development of motor skills are present in sports activities. Explosive strength can be defined as the ability to produce maximum force as soon as possible, and it represents an essential factor in activities where it is necessary to increase the acceleration of the body mass, the mass of specific body parts, or of an external object. The aim of study - to determine the effects of an experimental program on the explosive strength of lower limbs in male adolescents. Material and Methods. One hundred and one male adolescent (aged 19 years ± 6 months; body height 181.43 ± 7.42 cm; body mass 80.08 ± 10.07 kg) were recruited and randomly divided into two groups: experimental group (E; N=48) and control group (K; N=48). The E group performed the experimental program which lasted fifteen weeks and consisted of three 60-min training sessions per week. All participants were tested on Squat Jump (SJ), Countermovement Jump (CMJ), Countermovement Jump with arms (CMJa) and Continuous Jump with Straight Legs (CJSL). The four tests were performed using a Kistler force platform to measure Quatro Jump Bosco Protocol Version 1.0.9.2 and gave us data about the jump height, number of jumps for 15s, average power jump and peak power jump. The multivariate analysis covariance (MANCOVA) and follow up analysis covariance (ANCOVA) were used to analyze the data. Results. The results of MANCOVA showed statistically significant differences (p ≤ 0.001) between the E and K groups in all systems of variable lower limb explosive strength in male adolescents. In addition, results of ANCOVA showed statistically significant differences (p ≤ 0.001) in SJ, CMJ, CMJa and CJSL in favor of the E group compared to the K one. Conclusions. The results of this research show that a fifteen-week experimental program can lead to significant improvements in lower limb explosive strength in male adolescents.